Uczeń jako podmiot edukacji szkolnej. Perspektywa aksjologiczna = Students as subjects of school education. Axiological perspective - Pasterniak-Kobyłecka, Ewa (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
Each child is an autonomous subject and the co-creator of the educational process. The child`s activity and the tasks the child undertakes determine the realization of educational objectives. At school the student learns to exercise the rights and privileges and shapes the sense of responsibility for the proper conduct resulting from the assumed responsibilities.
Keywords: podmiot; podmiotowość; prawa ucznia; wartości; subject; subjectivity; student rights; values